In-plane cyclic behavior of structural insulated panel wood walls including slit steel connectors. (1st November 2018) - Purasinghe, Rupa; Dusicka, Peter; Garth, John S.; Dedek, Gennelle; Lum, Howard
Highlights: Performance of the conventionally connected SIP walls vs. that connected with slit steel connectors. Quasi-cyclic loading on SIP walls. Comparison with traditional wood frame walls. Increase of initial stiffness and higher average peak strength relative to standard walls. Failure modes of splitting of sill plate and fastener failure along sill plate and panel-to-panel connections. Abstract: The objective of this paper was to experimentally investigate the behavior of structural insulated panel (SIP) walls under in-plane cyclic loading and to test several panel-to-panel connections in order to measure their effect on the behavior of the walls. Each wall was constructed using two SIP panels with one top plate, one sill plate, two end plates, and a panel-to-panel connection. Each SIP panel had a 5.5 in. (14 cm) thick expanded polystyrene core sandwiched between two 4′ × 8′ (1.22 m × 2.44 m) sheets of 7/16″ (1.11 cm) oriented strand board. The top sill plates were split up between each panel in an effort to increase the potential for racking behavior of the walls and, therefore, the relative vertical displacement between the panels. In addition, as a preliminary study, three different steel connector configurations utilizing 26 gauge steel shear panels were considered in an effort to introduce additional ductility compared to more traditional block spline connection. From experimental observation of the wall with the block spline connection and the wall with no connection, the panel-to-panel connection was shown to contribute significant strength and stiffness to the wall system. The walls that were constructed with the first two configurations of the shear panels did not show any significant increase in either stiffness or ductility over the wall with the block spline. These walls also showed a decline in peak strength, which occurred at lower lateral displacements than the peak strength of the typical wall. For both of these cases, the shear panels yielded early and ruptured at the lateral deformation which caused peak load in each wall. The SIP wall implementing the third style of shear panel also did not demonstrate a significant increase in ductility as compared to the standard SIP wall. Despite the initially outlined potential, the preliminary study of implementation of the slit steel shear panels considered in this study did not significantly alter the performance of the conventionally connected SIP walls. Further study with stiff connectors capable of significant ductility prior to fracture would need to be implemented to realize the benefits of increased wall ductility.